Nanosecond pulsed fiber laser cleaning of natural marine micro-biofoulings from the surface of aluminum alloy. (20th January 2020) - Tian, Ze; Lei, Zhenglong; Chen, Xi; Chen, Yanbin; Zhang, Lai-Chang; Bi, Jiang; Liang, Jingwei
Abstract: Herein, environmentally effective nanosecond (30 ns) pulsed fiber laser cleaning technology was innovatively used to remove natural marine micro-biofoulings with the thickness of 61.7 ± 26.5 μm from the surface of aluminum alloy. The morphologies and chemical compositions of the uncleaned and cleaned surfaces of the samples were examined and analyzed by field emission scanning electron microscopy (FESEM), electron microprobe (EPMA), atomic force microscopy (AFM), and energy dispersive spectroscopy (EDS). The wettability of cleaned surface was studied by contact angle analyser. Successful cleaning of the aluminum surfaces to remove marine micro-biofoulings can be achieved by using different laser fluences (1.38–5.52 J/cm 2 ). The aluminum content of laser-cleaned surface was 88 wt% approximately, which reached up to 91.7% of that of the original substrate surface. Mechanism analysis indicated that laser-induced vaporization and ablation broke and eradicated of marine micro-biofoulings. The generated new surfaces were with free of damage and acceptable. At specific laser fluences (5.52 J/cm 2 ), the surface even had additional superhydrophobicity which provides the feasibility of antifouling in the periodic service. This work offers fundamental research and practical guidance for laser cleaning of marine micro-biofoulings on the surface of aluminum alloy. Graphical abstract: Image 1 Highlights: The Al alloy covered by marine micro-biofoulings was removed by laser cleaning. The cleaned surface showed a combination effect of both cleaning and micro-machining. Laser cleaning can be regarded as a marine antifouling tool in the future.